A NEW RECORD OF ETLINGERA PAUCIFLORA (ZINGIBERACEAE) IN JAVA, INDONESIA - Dini Puspitaningrum; W.A Mustaqim; Marlina Ardiyani (Reinwardtia, 2017)
PUSPITANINGRUM, D., MUSTAQIM, W. A. & ARDIYANI, M. 2017. A new record of Etlingera pauciflora (Zingiberaceae) in Java, Indonesia. Reinwardtia 16 (1): 1 - 4. — Etlingera pauciflora has been documented for the first time in Java, Indonesia, at Mount Honje, Ujung Kulon National Park, Banten. Description, figure as well as DNA barcodes are provided.